DEBT TAKING AND CHARITY-GIVING AMONG LOW-INCOME HOUSEHOLDS: STRENGTHENING RESILIENCE IN ISLAMIC PERSPECTIVE - Arsyianti, Laily Dwi; Kassim, Salina; Adeyemi, Adewale Abideen (Journal of Islamic Monetary Economics and Finance, 2018)
Households’ financial problem was perceived to be solved by taking other source of fund such as debt. In Islam, taking debt should be considered as the last resource when other sources were not available. Islam gives solution for those who have financial problem. Giving just small amount of money would give barakah to the giver. Charity-giving is not privilege for the rich people, but also for those in dire conditions. This paper attempts to explore whether low-income households’ perception on consecutive debt-taking influences their perception on regular charity-giving especially to achieve stipulated outcomes, i.e. households’ financial resilience. Structural Equation Modelling (SEM) is employed to analyse 1780 data from respondents across six areas in Indonesia. Low-income households perceived consecutive debt-taking to have negative relationship with regular charity-giving and positive relationship with outcomes (households’ financial condition and lifestyle satisfaction). Meanwhile, regular charity-giving has negative relationship with the outcomes when consecutive debt-taking intervene the relationship. Financial education and selection of financing institution have been proven to have relationships with variables which influence both regular charity-giving and consecutive debt-taking behaviours. As recommendation, charity education or sharing values should be included in the current financial education program. Formal financial institutions and social finance institution should also encourage supervision and continuously give financial education to social funds receivers.